Functionalism Paradigm in Second Language Writing: A Systematic Literature Review using Corpus-based Analysis - Pradita, Intan (SALEE: Study of Applied Linguistics and English Education, 2024)
This paper uses a corpus-based analysis systematic literature review to track the influence of functionalism paradigm in second language writing (SLW) over the last five years. The data were analyzed by using keywords and collocation analysis to map the closest association of functional paradigm to second language writing.  It was then reviewed manually and thematized based on the research questions as the framework. Based on a corpus of 46 Scopus indexed journals ranges from 2017-2022 this study reveals that the influence of functionalism paradigm does not directly affect to SLW. Functional paradigm spawned the concept of context which then be interpreted and manifested into functional linguistic approach. Thus, studies on SLW revolves around the application of systemic functional linguistics (SFL) to either teaching or assessing SLW. The elements of functionalism paradigm that affects to SLW are the basic assumption and the values of functional paradigm that perceived each variable in a text has a purpose. As an implication, second language writing composition using SFL focuses on text purpose and lexicogrammatical features. Functional linguists perceive language diversity in second language writing as functional, ensuring mutual intelligibility if communicative functions work effectively.